Meta‐analysis of genetic parameters for growth traits in meat, wool and dual‐purpose sheep breeds in the world using a random‐effects model. Issue 1 (12th December 2022) - Abasi‐Mousa, Sara; Varkoohi, Sheida; Joezy, Sahereh; Salary, Nader; Khansefid, Majid
Abstract: Background: There is large variation in genetic parameters in literature for growth traits in sheep. Reliable estimation of genetic parameters is required for developing breeding programmes. Objectives: The aim of this study was to aggregate results of different studies by meta‐analysis to improve reliability of estimated parameters. Methods: In the current study, 221 papers that have been published between 1995 and 2021 were reviewed. Using a random‐effects model in the Comprehensive Meta‐Analysis software, direct and maternal heritabilities, as well as, genetic and phenotypic correlations between growth traits were estimated in meat (M), wool (W) and dual‐purpose (D) sheep breeds. The growth traits in this study were birth weight, 3‐month weight, 6‐month weight, 9‐month weight and yearling weight. Results: The combined direct heritability was the lowest for birth weight (0.190 ± 0.004, 0.198 ± 0.003 and 0.196 ± 0.004 for M, W and D breeds, respectively) and the highest for yearling weight (0.264 ± 0.010, 0.304 ± 0.005 and 0.285 ± 0.020 for M, W and D breeds, respectively). The maternal heritability was the lowest for yearling weight (0.085 ± 0.003, 0.055 ± 0.002 and 0.052 ± 0.005 for M, W and D breeds, respectively) and the highest for 6‐month weight (0.240 ± 0.088, 0.164 ± 0.001 and 0.162 ± 0.006 for M, W and D breeds, respectively). The phenotypic and genetic correlations were lower between the weights measured at more distant intervals. The lowest genetic correlation was observed between birth weight and yearling weight (0.290 ± 0.051 for W breeds). Conclusions: The small standard errors could indicate that the aggregation of results from different studies improved the reliability of estimated parameters and reduced range of 95% confidence intervals. Hence, the results could be used with greater level of confidence in sheep breeding programmes. Abstract : There is large variation in genetic parameters in literature for growth traits in sheep, so aggregation of different studies results by meta‐analysis can improve reliability of estimated parameters. A meta‐analysis with 221 articles was carried out. Decrease in Standard errors could indicate that aggregation of results of different studies improved reliability of parameters and reduced range of 95% confidence intervals.